ANALISIS PENGARUH KEPEMIMPINAN DAN KEADILAN DISTRIBUTIF TERHADAP KEPUASAN KERJA (Studi kasus Pada Karyawan PT. Energi Mega Persada Tbk, Jakarta) - Rahmani, Ghaniyyu; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
The research aims to examine and analyze the influence of leadership anddistributive justice toward job satisfaction of employee in PT. Energi Mega Persada Tbk, Jakarta. Data collected through distribution of questionnaires and it is implemented to 139 employees of PT. Energi Mega Persada Tbk, Jakarta.Analysis of data in this research using the help of SPSS version 20. Asampling technique uses a survey method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic assumption test and double linear regression analysis, to verify and to prove the research hypothesis.Analysis result demonstrates that leadership have a positive influence toward job satisfaction. Distributive justice have a positive influence toward job satisfaction and leadership have a positive influence toward distributive justice.